Signal Molecule Hydrogen Sulfide (H2S) in Plants - İlkay YAVAŞ; Aydın ÜNAY (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
Hydrogen sulfide (H2S) is a gas known as toxic for years with the colorless formation and rotten egg odor. Hydrogen sulfide becomes phytotoxic for the plant when combined with other environmental stress conditions due to the high concentration of the effect on plant cells. Hydrogen sulfide plays a vital role in regulating various physiological processes such as stoma movements in plants, regulation of senescence in flowers and leaves, photosynthesis and germination. Various abiotic stress conditions such as heavy metal stress, drought, waterlogging, salinity, fungal infection, UV-B stress, cold and heat stress triggers the production of H2S. In response to environmental stresses, plants synthesize hydrogen sulfide via L-cysteine desulfhydrase (LCD), D-cysteine desulfhydrase (DCD), sulfate reductase (SIR), cyanoalanine synthesis (CAS) and cysteine synthesis (CS) and increase plant tolerance against these stress. Hydrogen sulfide produced by plants is also released to the atmosphere. For this reason, it is necessary to consider H2S as a signal molecule as well as a phytotoxin.